The Binding Prediction of 6-Paradol and its Derivatives on TRPV1 Agonist as a New Compound for Treating Painful Diabetic Neuropathy - Fajrin, Fifteen Aprila; Rahmayanti, Fina; Pratoko, Dwi Koko (Fakultas Matematika dan Ilmu Pengetahuan Alam Universitas Jember, 2020)
Ginger was reported to have a suppressive effect on pain in patients with Painful Diabetic Neuropathy (PDN). Our latest study revealed that 6-shogaol, one of the ginger components, had the best affinity in the Transient Receptor Potential Vanilloid 1 (TRPV1), a key receptor in PDN). Paradol, which obtained from gingerol and shogaol metabolism, also had potent activities in several diseases, compared to the other derivatives of gingerol and shogaol. However, shogaol and paradol is very similar in chemical structure with only different in one double bond in 4-5 position. Until now there is no explanation about paradol mechanism in TRPV1. Based on this, our study was designed to predict the activity of 6-paradol and its derivatives to TRPV1 as target receptor in PDN using in-silico model. 2-paradol, 4-paradol, 6-paradol, 8-paradol and 10-paradol were used as ligands. Capsaisin, the agonist of TRPV1, was used as a native ligand in this study. TRPV1 was obtained from protein data bank (PDB). Ligand bond prediction and affinity was performed using Molegro Virtual Docker. The results showed 2-paradol, 4-paradol, 6-paradol, 8-paradol and 10- paradol had good affinity against TRPV1. These result indicated that 6-paradol and the derivatives had potential as a drug compound for PDN therapy.Keywords: ginger, 6-paradol, painful diabetic neuropathy, trpv1.